Distinct characteristics and prognosis of IgA nephropathy patients with nephrotic syndrome: a propensity score-matched cohort study - Jiang, Yuanyuan; Chen, Pei; Zhao, Wenjing; Liu, Lijun; Shi, Sufang; Lv, Jicheng; Zhang, Hong (Frontiers in Medicine, 2024)
Introduction IgA nephropathy (IgAN) is the most prevalent primary glomerulonephritis globally. While nephrotic syndrome (NS) is uncommon in IgAN, its significance remains unclear. Methods We conducted a retrospective analysis of 170 IgAN patients, classifying them into NS (n = 85) and non-NS (n = 85) groups. Our study aims to compare their clinical characteristics, treatment responses, and prognoses. Patients were selected based on renal biopsy from 2003 to 2020. Propensity score matching ensured comparability. Clinical, pathological, and immunological data were analyzed. Composite endpoints were defined as end-stage kidney disease (ESKD) or a 30% decline in estimated glomerular filtration rate (eGFR). Results NS patients showed higher eGFR (74.3 ± 36.8 vs. 61.5 ± 33.6 mL/min.1.73 m2, p = 0.02), severe hematuria (35.0 (4.7,147.5) vs. 4.0 (1.8,45,0) cells/μl, p < 0.001), severe foot process effacement (p = 0.01), and lower C3 levels (1.0 ± 0.3 vs. 1.1 ± 0.2 g/L, p = 0.03). In contrast, the non-NS group had higher BMI (24.3 ± 4.0 vs. 26.8 ± 3.7 kg/m2, p < 0.001) and elevated serum uric acid levels (376 (316,417) vs. 400 (362, 501) mmol/L, p = 0.001), suggesting metabolic factors might contribute to their condition. Both groups exhibited similar MESTC scores. NS patients had higher complete remission rates (26.2% vs. 14.1%, p = 0.04). Cox regression revealed NS independently associated with a higher risk of composite endpoints (HR = 1.97, 95% CI 1.05–3.72, p = 0.04). Linear mixed models did not show significant eGFR trajectory differences. Discussion This study has established that IgAN patients with NS exhibit distinct characteristics, including active disease and increased complement activation. NS is independently associated with a poorer prognosis, emphasizing the need for targeted interventions in this subgroup.